Studi Kritis atas Hadis “Sab’ah Ahruf” - Rahmat Nurdin; Muhammad Nur Murdan (PAPPASANG, 2021)
The Hadis talking about “unzila al-Qur’an ‘ala sab’ah ahruf” has been interpreted by some Islamic scholars. Every scholar has different opinion. According to this,  it is important to re-read for making clear what “sab’ah ahruf” meaning is. This paper would like to analyze this hadis on steps; external criticism, internal criticism and syarh al-hadis (understanding). In the conclusion, based on the al-Razi’s view, this mini-research shows that “sab’ah ahruf” is about the sevent differences in Quranic reading. Then, flexibility in reading the Quran to make it easier to be read indicates that Quran is possible to be interpreted in different approaches to make it easier to be understood.